Synthesis and swelling behavior of rice husk based superabsorbent polymer composite - Muhamad Shahir, Hasan (2010)
Superabsorbent polymer composites (SPC) based on acrylic acid and rice husk (RH) was synthesized through a solution polymerization to improve water absorbency and reduce production cost. The SPC was characterized using Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM). The objectives of this research to synthesis RH based SPC by determine the effect of amount RH, and crosslinker agent N,N’-methylenebisacrylamide (MBA), towards swelling behavior of SPC in water and saline solution. Experiments have been done by used RH contents in range of 576 to 864 mg and for amount of NMBA content evaluate in range of 11.44 to 22.88 mg. The swelling behaviors have been investigated by measured the water absorption of rice husk-g-poly (acrylic acid). The water absorbency determined by using tea-bag method. The result showed as the amount of RH was increased, the water absorbency also increase. The maximum absorbency 4.8745 g/g in distilled water was obtained. The effect of MBA content result show the water absorption increases with increase of the cross-linker amount in the range of from 11.44 to 14.3 mg. Then, water absorption decreases with further increased of cross-linker amount. The maximum absorbency of 4.221 g/g in distilled water was obtained. The swelling behavior in saline solution also has been investigated. The result shows that water absorbency give insignificant value in saline solution compare to absorbency value in distilled water.